VD_FINDINFO Décision / 2013 / 312 vom 25. Dezember 2012 - VD Tribunal cantonal (2012)
DÉTENTION PRÉVENTIVE, RISQUE DE RÉCIDIVE, ACTE D'ORDRE SEXUEL AVEC UN ENFANT | 187 CP, 221 al. 1 let. c CPP (CH), 227 CPP (CH), 393 al. 1 let. c CPP (CH)